Primary gastric choriocarcinoma with multiple metastases - A case report and literature review of carcinogenesis - Yiqin Xiong, MD, PhD; Michelle X. Yang, MD, PhD (Elsevier, 2019)
Primary gastric choriocarcinoma (PGC) is a rare gastric malignancy that accounts for <0.1% of all gastric malignancies. We reported a case of primary gastric choriocarcinoma in a 47-year-old female who presented with chronic gastric ulcer and upper gastrointestinal bleeding and severe anemia. Endoscopy showed an ulcerated mass in the gastric fundus that was biopsied and consistent with a choriocarcinoma by histomorphology and immunohistochemistry studies. Subsequent computed tomography (CT) scans revealed multiple brain lesions. The largest frontal lobe hemorrhagic lesion was resected and histology revealed metastatic choriocarcinoma. Two months prior to her presentation, the patient underwent right lower lobectomy of the lung and was diagnosed with primary lung adenocarcinoma and a synchronous high grade carcinoma with trophoblastic differentiation at an outside hospital. The patient had no history of molar pregnancy and no apparent adnexal lesions were found by CT and pelvic examinations. Due to the advanced metastatic disease, the patient started chemotherapy with Cisplatin and Etoposide. Both the gastric choriocarcinoma and brain metastasis showed aberrant strong nuclear p53 expression. Due to the rarity of primary gastric choriocarcinoma, a thorough literature review was performed and the hypotheses for the carcinogenesis of primary gastric choriocarcinoma were discussed. Keywords: Primary gastric choriocarcinoma, Metastasis